Efektivitas ekstrak buah senduduk (Melastoma malabathricum l.) sebagai pewarna apusan darah tepi - Iqlila Romaidha; Mega Silvia Madani; Larantika Hidayati; Rima Agnes Widya Astuti (Jurnal Kedokteran Universitas Palangka Raya, 2024)
Blood comes from the Greek words hemato, hemo, and haima. Blood has an important role in human life. One of the examinations for diagnosing disease is a peripheral blood smear. The smear method is a microtechnical method used to make preparations. Guaranteeing the quality of the examination of blood smears is the quality of the coloring of peripheral blood smears. Giemsa dye is the most commonly used for peripheral blood smears. Giemsa contains chemicals including methylene blue, azur, and eosin. Methylene azur and eosin provide color in the cell nucleus, as does methylene blue, a cytoplasmic dye. Giemsa is not environmentally friendly and has quite high prices. This study aims to determine the effectiveness of senduduk fruit extract with concentrations of 20%, 40%, 60%, 80%, and 100% as an alternative to Giemsa staining in peripheral blood smears. The research method is descriptive-qualitative with a true experimental research design. The extract was made using the maceration extraction method, using a rotary evaporator as a means of concentrating the senduduk extract. In research that has been carried out at each concentration used, the morphology of erythrocytes is very clear. At a concentration of 100%, platelets are clearly visible. The single extract at concentrations of 40%, 60%, and 80% of the cytoplasm still appeared colored. Meanwhile, leukocyte granules were not stained at all concentrations. The most optimal coloring for senduduk fruit extract is coloring at a concentration of 80%, which is quite good at coloring red blood cells and platelets. A concentration of 100% has a clear morphology of blood cells and platelets that can be differentiated from the others